Improving English Persuasive Writing in Malaysia: A Recommendation - Farous Izwan Abdul Aziz; Syahrul Nizam Salam; Seriaznita Mat Said (Asian Scholars Network, 2023)
Persuasive writing is a complex form of written discourse, requiring the writer to justify his stance with a strong argument. The problems students experience when attempting persuasive writing include poor organization, lacking support in their arguments and immature language. The purpose of this paper is to recommend a model to help Malaysian secondary school students improve their persuasive essay writing. 150 students from three secondary schools in the Hulu Klang Area were selected for this study and instructed to submit an essay according to a set of writing prompts provided by the researcher. Toulmin’s Model was employed to analyse the essays by identifying the persuasive elements that were utilized by the students in their essays. The findings revealed that the students’ proficiency level significantly affected the persuasive writing features that they employ in their essays and the numerous factors encompassing teachers’ pedagogical approach, general knowledge and reading habits influenced the students’ persuasive writing ability. Hence, the recommendation put forth by this paper is to integrate Toulmin’s Model with classroom practice so that students should be able to master the structure of persuasive arguments which will subsequently improve their persuasive writing strategies and nurture their critical thinking skills.